Approximation-free appointed-time tracking control for marine surface vessel with actuator faults and input saturation. (1st February 2022) - Zhu, Cheng; Zhang, Enhua; Li, Jun; Huang, Bing; Su, Yumin
Abstract: This paper investigates the tracking control problem for the marine surface vessel (MSV) under external disturbances, parametric uncertainties, actuator faults, and saturation constraints. The objective is to achieve the approximation-free prescribed performance control with appointed-time convergence. For this purpose, a new appointed-time performance function is designed, and a modified backstepping control design process is conducted. By means of the above contributions, a tracking control scheme possessing the following three features is developed. First, the derived control scheme can characterize the transient and steady-state performance quantitatively a priori. Unlike the conventional prescribed performance control, the appointed-time tracking performance can be guaranteed without the knowledge of initial system conditions. Second, the control design has high robustness against external disturbances and parametric uncertainties. Particularly, the auxiliary compensation system applied for lumped uncertainties is dropped out here such that the control design is simplified. Third, the derived control scheme has both fault-tolerant and anti-saturation merits. Numerical simulations are provided to support the analysis. Highlights: A new performance function is designed to obtain the appointed-time tracking performance. Besides, the requirement of the knowledge of exact initial tracking conditions is omitted. A modified backstepping method is conducted such that the auxiliary compensation system applied for lumped uncertainties can be dropped out. The derived control scheme has both fault-tolerant and anti-saturation merits.